A functional NPSR1 gene variant and environment shape personality and impulsive action: A longitudinal study. (March 2014) - Laas, Kariina; Reif, Andreas; Kiive, Evelyn; Domschke, Katharina; Lesch, Klaus-Peter; Veidebaum, Toomas; Harro, Jaanus
Neuropeptide S and its receptor NPSR1 are involved in the regulation of arousal, attention and anxiety. We examined whether the NPSR1 gene functional polymorphism Asn 107 Ile (rs324981, A>T) influences personality, impulsivity, and attention-deficit/hyperactivity disorder (ADHD)-related symptoms in a population-representative sample, and whether any eventual associations depend on age, sex, family relations and stressful life events (SLE). We used self-reports or teachers' ratings for both the younger ( n =593) and older ( n =583) cohort of the longitudinal Estonian Children Personality, Behaviour and Health Study. Males with the TT genotype displayed more ADHD-related symptoms. Adaptive impulsivity and Extraversion increased the most from age 18 to 25. While highest increases were observed in AA men, TT women exhibited the largest decreases. For participants with the AA genotype, Warmth in family was inversely associated with Neuroticism, and positively associated with Extraversion and Adaptive impulsivity. High exposure to SLE increased impulsivity and ADHD scores in TT genotype subjects. We conclude that the NPSR1 A/T polymorphism is associated with impulsivity, ADHD symptoms and personality, mirroring the activity- and anxiety-mediating role of NPSR1 . Heterozygous individuals were the least sensitive to environmental factors, whereas subjects with the AA genotype and TT genotype reacted to different types of environmental adversities.